REINVIGORATING CULTURAL LANDSCAPES FOR PLANNING CULTURAL TOURISM IN BALI - I Made ADHIKA; I Dewa Gede Agung Diasana PUTRA (Geo Journal of Tourism and Geosites, 2020)
A cultural landscape, a configuration produced by human actions and cultural structures in a physical setting, has a significant role to play as a vital feature of cultural tourism in Bali. However, this configuration has become the most heavily commoditized elements of the development of tourism. Construction of tourist amenities has exploited the notion of a cultural landscape that has been integrated into cultural practices, the environment and agriculture. This development and planning are a paradoxical phenomenon and a challenge for people to retain the identity of their cultural landscape while also seeking economic benefits from tourism. The struggle between the protection of the identity of the cultural landscape translated and manifested in the context of agriculture and its transformation in the context of designing tourist facilities has shaped the fundamental argument for preservation. Since there are different cultural traditions and practices in many Balinese cultural landscapes, the relationship between tourism and the diversity of cultural areas has become a key objective in the development of tourism and planning tourist facilities. This paper explores the current struggles between the concepts of tourism development and planning, and the conservation of Bali's cultural landscape. The paper argues that the focus of Bali's tourism development is to maintain and reinvigorate the integration of natural landscapes and cultural practices that present a persistent link between the agricultural system and religious practices.